PTH-214 An audit reviewing the impact of a nutrition multi-disciplinary team on wastage of adult parenteral nutrition bags. (22nd June 2015) - Shah, S; Callaby, H; Hoey, S; Thompson, L; Dubois, P; Vincent, R
Abstract : Introduction: At our hospital prior to April 2014, patients commenced on parenteral nutrition (PN) were reviewed on a daily basis by the chemical pathology registrar and once weekly on a multi-disciplinary nutrition team (MDT) ward round. PN was prescribed and manufactured in advance where possible to help facilitate the work flow within the pharmacy aseptic unit. In April the nutrition MDT recruited a nutrition clinical nurse specialist (CNS) and introduced twice weekly consultant led MDT ward rounds. In addition, daily reviews of all PN patients are done by the CNS and a pharmacist with the registrar, for daily prescriptions. The aim of this audit was to assess the impact of the enhanced nutrition support MDT on: (1) the percentage of PN bags used for the intended patients, (2) the projected annual financial cost of wasted PN, (3) the percentage of PN bags that have been reallocated where cold chain storage is assured, (4) the cost saving incurred as a result of reallocating wasted PN bags. Method: Prospective data was collected on adult PN bags over a three month period between October – December 2014. All PN bags ordered from an external provider and standard PN bags from the aseptic pharmacy department were included. Any PN bags from other hospitals and home PN bags were excluded. Information captured included: total number of adult PN bags, type of PN bag, reasons for wastage or return, why bag could not be reallocated, number of bags reallocated and the cost of the PN bag. The price for each PN bag was calculated based on the cost breakdown from the monthly PbR PN reporting for aseptic services. Results were compared to data collected during a previous audit undertaken between April–July 2014. Results: 627 PN bags were ordered during the audit period. Out of which 91% (n = 568/627) were used for intended patient (an increase of 1%); the financial cost of wasted PN was £6, 217 per annum (a decrease of 62%); 69% (n = 41/59) were reallocated (increase of 5%); and the cost saving was £8, 926 per annum (an increase of 37%). Conclusion: The inclusion of a CNS and a pharmacist to the daily ward rounds as well as daily prescribing of adult PN bags significantly improved the utilisation of PN bags appropriately and minimised waste. A system to highlight which PN bags are available for reallocation should be introduced locally to avoid available bags not being utilised. Disclosure of interest: None Declared.